Critical views of the poet Hussein Mardan (Journal of the College of Basic Education, 2022)
Poet critic Hussein Mardan presented documented data in his critical projectRelationship. between the text and the reader; It is a serious relationship; that requires that there be between him andThe text orbits in which their tools are w and the critic's tools are the critical data available betweenhis hands; The text, in the opinion of the poet, cannot have an existence or a destiny without the reader.Because the reader is a producer of what he monitors, and then he reshapes the text according to what this endsThe relationship between them ' is a relationship of transformation and interaction; competition and participation; And agreement and antagonism goThe reader and the text together, and all means of identification and self-openness are achieved for them.